Comparison of glycosylated haemoglobin, blood pressure, and anthropometric measurements depending on gender and bodyweight state in adolescents - Vivas, Jorge Carlos; Castillo Paredes, Antonio Jonathan.; Gómez Galán, Rafael.; Muñoz Bermejo, Laura.; Mendoza Muñoz, María.; Adsuar Sala, José Carmelo.; Pastor Cisneros, Raquel.; Calle Guisado, Violeta. (MDPI, 2022)
Background/Objective: The greatest anthropometric and physiological changes occur during adolescence. Assessment of growth patterns is necessary to prevent future health risks. Aims: To describe the values of glycosylated haemoglobin (HbA1c), systolic (SBP) and diastolic (DBP) blood pressure, triceps skinfold, and abdominal circumference according to gender and age (between 12 and 17 years), as well as explore the differences between body weight conditions. Methods: A descriptive cross-sectional study was carried out, including 4130 adolescents between 12 and 17 years old. SBP and DBP, HbA1c, triceps skinfold, and abdominal circumference were evaluated. Results: Significant differences were observed between males and females for HbA1c (p < 0.001), SBP (p < 0.001), triceps curl (p < 0.001), and abdominal circumference (p < 0.001), independently of the age group. Regardless of gender and age groups, significant differences were observed between overweight/obese and normal-weight adolescents in SBP (p < 0.001), DBP (p < 0.001 to 0.009), triceps skinfold (p < 0.001), and abdominal perimeter (p < 0.001). Conclusions: Our findings revealed higher SBP, DBP, triceps skinfold, and abdominal circumference in overweight/obese adolescents compared to normal-weight adolescents in both genders.
Modelos de series de tiempo para predecir el número de casos de variantes dominantes del SARS-COV-2 durante las olas epidémicas en Chile
Keywords: Bodyweight; Glycosilated haemoglobin; Adolescentes; Antropometría; Presión sanguínea; Salud